Hard-working in general but lazy at home?: generalized big five traits and relationship-specific traits in romantic couples over time - Bühler, Janina Larissa; Wrzus, Cornelia; Weidmann, Rebekka; Wünsche, Jenna; Burriss, Robert P.; Grob, Alexander (Journal of research in personality, 2021)
To acknowledge the significance of contexts for personality, this study focused on personality in romantic relationships and the concept of relationship-specific traits. Specifically, we were interested in how relationship-specific traits (i.e., how people report to be in their relationship) relate to generalized Big Five traits, and whether both constructs codevelop over time. We computed dyadic bivariate latent growth curve models, using data from 551 couples (Mage = 32.23 years) over 1 year. The findings indicated that generalized traits and relationship-specific traits were positively correlated in their intercepts but did not codevelop over time. Furthermore, baseline relationship satisfaction explained variance in traits, particularly in relationship-specific traits. These findings have implications for how to study personality development in the romantic relationship context.
Gesehen am 17.08.2021